If it ain't broke, don't fix it: positive versus negative emotion regulation in daily life and depressive symptoms - Müller, Ilka; Prüßner, Luise; Holt, Daniel; Zimmermann, Verena; Schulze, Katrin; Strakosch, Ana-Maria; Barnow, Sven (Journal of affective disorders, 2024)
Background - Despite the importance of positive emotions for affective psychopathology, prior research primarily focused on negative emotion regulation. To address this gap, this ecological momentary assessment study compared a broad set of emotion regulation strategies in the context of positive versus negative emotions regarding their effectiveness and associations with depressive symptoms. - Methods - We analyzed data from 1066 participants who were notified five times daily for seven consecutive days to complete a smartphone survey assessing their predominant emotions, strategies to regulate them, and subsequent emotional outcomes. - Results - Findings show that the effectiveness of most regulation strategies depended on whether the emotional context was positive or negative. While acceptance and savoring predicted improved emotional outcomes across emotional contexts, reappraisal and problem-solving were associated with deteriorated emotional outcomes and increased depressive symptoms when regulating positive but not negative emotions. - Limitations - Future studies should replicate our findings in demographically and culturally diverse clinical samples to improve generalizability. - Conclusion - These results emphasize that strategies effective for regulating negative emotions may be less helpful in the context of positive emotions. Thus, context-specific interventions may be a promising approach to improve the treatment of affective disorders.
Online veröffenticht: 19. Dezember 2023, Artikelversion: 9. Januar 2024
Gesehen am 08.04.2024